Influence of directional positive Darwinian selection-driven evolution on arboviruses Dengue and Zika virulence and pathogenesis - Durães-Carvalho, Ricardo; Ludwig-Begall, Louisa F.; Salemi, Marco; Lins, Roberto D.; Marques, Ernesto T.A. (Molecular phylogenetics and evolution, 2019)
[Display omitted] •DENV and ZIKV evolution are driven essentially by directional positive selection.•DENV and ZIKV polyproteins are under an intense directional evolution pressure.•We mapped mutations associated to changes in DENV and ZIKV virulence and pathogenesis.•The impact of certain mutations on DENV and ZIKV outbreaks in the Americas is shown. Dengue (DENV) and Zika (ZIKV) viruses are antigenically and evolutionarily related; immunological cross-reactions between them have been associated to both cross-protection and infection-enhanced mechanisms. Here, DENV-1-4 and ZIKV were investigated through Bayesian coalescent-based approaches and selection-driven Darwinian evolution methods using robust datasets. Our findings show that both DENV and ZIKV, driven essentially by directional positive selection, have undergone evolution and diversification and that their entire polyproteins are subject to an intense directional evolution. Interestingly, positively selected codons mapped here are directly associated to DENV-1-2 virulence as well as the ZIKV burgeoning 2015–16 outbreak in the Americas, therefore, having impact on the pathogenesis of these viruses. Biochemical prediction analysis focusing on markers involved in virulence and viral transmission dynamics identified alterations in N-Glycosylation-, Phosphorylation- and Palmitoylation-sites in ZIKV sampled from different countries, hosts and isolation sources. Taking into account both DENV-ZIKV co-circulation either into and/or out of flavivirus-endemic regions, as well as recombination and quasispecies scenarios, these results indicate the action of a selection-driven evolution affecting the biology, virulence and pathogenesis of these pathogens in a non-randomized environment.